An evaluation of injury photography practices in Sexual Assault Referral Centres (SARC). (October 2022) - Smith, P.; Marsh, N.; Bayley, S.; Volpellier, M.
Abstract: A review was carried out of injury photography methods in a Sexual Assault Referral Centre (SARC). An initial case study review was conducted with a London based SARC where injury photography of sexual assault complainants was routinely undertaken, and has been for over six years. These images are taken by medical staff using 'point and shoot' compact cameras. Following this and to gain an impression of the national picture, a short survey was sent to 58 SARCs to determine the use of photography in capturing injuries, noting the regularity of its use and the specific types of photographic equipment used. 40 out of the 58 SARCS replied and responses show only three routinely use digital photography as a means to document bodily images. The technique was employed, but not routinely or only infrequently, at a further 20 SARCs. In a further seven centres digital photography was only used for self-referral cases to document general body images, the client's being photographed by the police photographers in any case with police involvement. Five SARCs organised training for their examiners on a Digital Single Lens Reflex (DSLR) photography course, none of which subsequently use their DSLR camera to document bodily injuries. Interestingly, two SARCs report using a colposcope as their camera when they consider that photography 'can't wait' as, for example, when they consider the injury may well disappear by the time police photography can be arranged. The review suggests compact cameras require shorter training, are cheaper to buy, easier to use and produce images suitable for use in court. Highlights: Reviews the injury imaging and capture process in UK SARCs. Using a case example, introduces basic imaging capturing processes using compact cameras. Outlines practical benefits of having initial image capture for injuries available at the SARC. Recommends a review of injury capture methodologies across the SARC. Findings indicate DSLR cameras are not requiredtraining and purchase is often wasted with cameras going unused.